Characterization of the airflow field in the rotor spinning unit based on a novel experimental approach and numerical simulation. Issue 7 (April 2021) - Shi, Qianqian; Akankwasa, Nicholus Tayari; Zhang, Yuze; Wang, Jiang; Wang, Jun; Lin, Huiting
It is very challenging to experimentally characterize and verify the airflow in the rotor spinning machine because the process takes place in an enclosure. In an attempt to portray the process, we present a methodology that combines a novel experimental approach and numerical techniques. We developed a model unit and used colored smoke to mimic the airflow behavior practically, measured the air pressure, and compared the results to the simulation data. Three state conditions, namely suction and rotation (the regular rotor spinning operation, (Case 1)), without rotation (Case 2), and without suction (Case 3), were adopted to investigate the formation mechanism of the airflow field in the rotor spinning unit based on two operating conditions. Results show that, in a regular state, the airstream accelerates rapidly in the transfer channel under the dominant action of air suction at the rotor outlet and crashes clockwise to the rotor wall with the joint action of two operating conditions. In the rotor, the airflow flows clockwise with the velocity distribution of a multi-ring gradient due to the dominant action of high-speed rotor rotation. Analytics from the air pressure indicate that while the air pressure in the rotor is mainly controlled by the action of the air suction mechanism, it is also affected by the superposition action of the rotation mechanism. This approach is groundbreaking for rotor spinning machine optimization and is anticipated to trigger more insights that will lead to fundamental research in the spinning industry and beyond.